Ship stability, dynamics and safety: Status and perspectives from a review of recent STAB conferences and ISSW events. (1st April 2016) - Bačkalov, Igor; Bulian, Gabriele; Cichowicz, Jakub; Eliopoulou, Eleftheria; Konovessis, Dimitris; Leguen, Jean-François; Rosén, Anders; Themelis, Nikolaos
Abstract: In Naval Architecture, the concept of "stability" has a very wide meaning, embracing ship stability fundamentals with ship dynamics and ultimately ship safety. As such, the subject is of paramount importance for its wide implications on design and operation of ships and floating units. Research in this field has, therefore, an important impact on the fleet safety, and the International Conferences on Stability of Ships and Ocean Vehicles (STAB Conferences) and the International Ship Stability Workshops (ISSW) are certainly the venues where expertise and contemporary developments in this specific field tend to be collected and thoroughly debated. With the aim of analysing the current status and possible future perspectives of research in the field of ship stability, dynamics and safety, this paper provides an extensive review of the findings presented at STAB Conferences and ISSW events in the period 2009–2014. The reviewed material is organised according to a set of identified macro-topics of research. On the basis of the reviewed material, consolidated research topics as well as emerging subjects are laid out, and ideas for possible future research are also brought forward. Discussion is also provided regarding the link between research and educational aspects. Highlights: An overview of research on ship stability, dynamics and safety, is presented. Papers presented at the International Conferences on Stability of Ships and Ocean Vehicles (STAB Conferences) and at the International Ship Stability Workshops (ISSW) in the period 2009-2014 are reviewed. Consolidated and emerging research topics are highlighted. Ideas for possible future research are provided. The link between research and educational aspects is discussed.